CHECK LIST OF ARMENIAN APHIDS (HEMIPTERA: APHIDOMORPHA) - Stepanyan, Ilona; Barjadze, Shalva; Karagyan, Gayane; Kalashian, Mark (Zootaxa, 2023)
This paper presents a checklist of aphids of Armenia. Nowadays, 203 species of aphids belonging to 83 genera, 10 subfamilies, two families and two superfamilies are known, of which nine species are recognized in Armenia for the first time: Aphis cephalariae Barjadze, A. chloris Koch, A. solanella Theobald, A. urticata Gmelin, A. wellensteini (Börner), Brachyunguis harmalae Das, Macrosiphoniella millefolii (De Geer), Microlophium carnosum (Buckton), and Metopeurum buryatica (Pashtshenko). Twelve alien aphid species are cited in the paper.